2019
DOI: 10.1002/hbm.24613
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal characterization of perfusion in the aging brain and associations with cognition and neural structure

Abstract: Cerebral perfusion declines across the lifespan and is altered in the early stages of several age‐related neuropathologies. Little is known, however, about the longitudinal evolution of perfusion in healthy older adults, particularly when perfusion is quantified using magnetic resonance imaging with arterial spin labeling (ASL). The objective was to characterize longitudinal perfusion in typically aging adults and elucidate associations with cognition and brain structure. Adults who were functionally intact at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 94 publications
6
48
0
Order By: Relevance
“…These regions comprise the default mode, dorsal attention and frontoparietal networks associated with attention and executive functions (22). A recent study also found positive associations between the executive function composite score and CBF in dorsolateral prefrontal cortex ( Staffaroni et al, 2019 ). Therefore, it is not surprising that relative CBF in leptoMCA territory was correlated with the executive function composite score.…”
Section: Discussionmentioning
confidence: 90%
“…These regions comprise the default mode, dorsal attention and frontoparietal networks associated with attention and executive functions (22). A recent study also found positive associations between the executive function composite score and CBF in dorsolateral prefrontal cortex ( Staffaroni et al, 2019 ). Therefore, it is not surprising that relative CBF in leptoMCA territory was correlated with the executive function composite score.…”
Section: Discussionmentioning
confidence: 90%
“…The importance of sufficient cerebral perfusion in maintaining proper cognitive functioning is recently highlighted in both cross-sectional and longitudinal studies of otherwise cognitively intact healthy population. For an example, a recent 2-year long longitudinal ASL study showed that healthy individuals with decline in GM CBF present with concurrent decline in other markers of brain aging including lower cortical volume, worse WM microstructural integrity, and greater appearance of WM hyperintensities (27). More importantly, the longitudinal GM CBF decline was associated with worsening of the cognitive processing speed (27).…”
Section: Discussionmentioning
confidence: 99%
“…For an example, a recent 2-year long longitudinal ASL study showed that healthy individuals with decline in GM CBF present with concurrent decline in other markers of brain aging including lower cortical volume, worse WM microstructural integrity, and greater appearance of WM hyperintensities (27). More importantly, the longitudinal GM CBF decline was associated with worsening of the cognitive processing speed (27). Reduction in cerebral perfusion has been also hypothesized as early marker of multiple neurodegenerative diseases, greater cerebral protein accumulation, and as a predictor of dementia development (28).…”
Section: Discussionmentioning
confidence: 99%
“…While 2 studies investigated associations between baseline WMH volume and change in either subregional 15 or global 37 CBF, one study considered associations between change in WMH volume and change in cortical grey matter CBF. 36 Fifteen studies used ASL 6-8, 10, 14, 15, 19, 20, 25, 27, 30, 32, 34-36 , 3 used CT perfusion 18,28,29 , 2 used dynamic susceptibility contrast (DSC) MRI 9,37 , one study each used SPECT 21 , phase contrast MRI 22 , CT angiography/digital subtraction angiography, 31 PET, 23 and a combination of CT and DSC MRI 12 . Five studies used transcranial Doppler ultrasound 16,17,24,26,33 .…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Longitudinal analyses of WMH and CBFThe largest of the three new longitudinal studies (Nylander et al 2017)37 in a cohort of 406 randomly selected 75 year old participants at baseline and 252 at follow-up, found no significant association between baseline CBF with WMH progression at a five year follow-up when adjusting for baseline WMH and sex(Table 4). In 136 functionally normal older individuals, Staffaroni et al(2019)36 found that longitudinal reductions in global CBF were associated with increasing WMH burden, adjusting for age, sex and education Promjunyakul et al (2018) 15 ,. in 52 cognitively healthy older participants, found that lower baseline CBF within the PVWMH penumbra was associated with WMH growth at follow-up, while reduced white matter perfusion remained predictive of PVWMH but not DWMH progression, adjusting for age and sex.…”
mentioning
confidence: 99%